Vulvar Lymphangioma Arising in the Setting of May–Thurner Syndrome - Surekha Bantumilli; Ian Flyke; Muthu Kumar Sakthivel; Christine E. Bookhout (Case Reports in Vascular Medicine)
This case report describes an instance of vulvar lymphangioma occurring in the setting of May–Thurner syndrome (MTS), an association between two vascular conditions that we do not believe has been previously reported. Lymphangioma, also known as lymphatic malformation, is a benign lesion typified by dilatation of endothelial-lined lymphatic channels involving the skin and subcutis, which can occur either as a congenital abnormality or as a result of acquired damage to lymphatic channels. Lymphangioma is a rare lesion in the vulva. MTS, also known as iliac vein compression syndrome or Cockett’s syndrome, is a condition of left iliac vein obstruction due to overriding the right common iliac artery which can lead to iliofemoral deep vein thrombosis. In this report, we describe the case of a 29-year-old woman with MTS diagnosed at 7 years of age with poor lymphatic drainage and pelvic pain requiring left iliac vein stenting. She presented with left vulvar discomfort and chronic lower extremity edema and was found to have warty vulvar masses, with histopathological examination showing lymphangioma of the vulva. We believe that this is the first report of vulvar lymphangioma recognized in the setting of MTS, and we will discuss the clinical features, etiology, and possible pathophysiologic association between these two entities.